Distribution of entangled photon pairs over few-mode fibers. Issue 1 (December 2017) - Cui, Liang; Su, Jie; Li, Xiaoying; Ou, Z.
Abstract Few-mode fibers (FMFs) have been recently employed in classical optical communication to increase the data transmission capacity. Here we explore the capability of employing FMF for long distance quantum communication. We experimentally distribute photon pairs in the forms of time-bin and polarization entanglement over a 1-km-long FMF. We find the time-bin entangled photon pairs maintain their high degree of entanglement, no matter what type of spatial modes they are distributed in. For the polarization entangled photon pairs, however, the degree of entanglement is maintained when photon pairs are distributed inLP 01 mode but significantly declines when photon pairs are distributed inLP 11 mode due to a mode coupling effect inLP 11 mode group. We propose and test a remedy to recover the high degree of entanglement. Our study shows, when FMFs are employed as quantum channels, selection of spatial channels and degrees of freedom of entanglement should be carefully considered.